2007
DOI: 10.6090/jarq.41.95
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Fish Species Cultured in Mangrove Brackish Area to Piscine Nodavirus

Abstract: Susceptibility of orange-spotted grouper Epinephelus coioides, Asian sea bass Lates calcarifer, mangrove red snapper Lutjanus argentimaculatus, milkfish Chanos chanos, and rabbitfish Siganus guttatus to piscine nodavirus from orange-spotted grouper was studied by experimental infection. The fish were intraperitoneally injected with 0.05 mL of the filtrate homogenate of infected organs from diseased grouper at 10 6.8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similarly, interspecies horizontal transmission has also been found between European sea bass and gilthead sea bream reared on the same farm (Castri et al, 2001) and in experimental trials between Asian seabass and brown-marbled grouper . In this study, when exposed to an immersion challenge with a pure culture of betanodavirus, a high percentage of cumulative mortality in the challenge group with manifestations of characteristic clinical signs and conspicuous histopathological lesions has been achieved, which was in accordance with the results reported by Boonyaratpalin et al (1996), Breuil et al (2001, Aranguren et al (2002) and Maeno et al (2007) and Manin and Ransangan (2011) and confirmed the horizontal transmission of betanodavirus through water by immersion exposure. When the Murray cod larvae were imported from the Australian fish farm, viral nervous necrosis virus, Megalocytivirus and Ranavirus detection were carried out by customs using PCR methods.…”
Section: Bath Challenge Experimentssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, interspecies horizontal transmission has also been found between European sea bass and gilthead sea bream reared on the same farm (Castri et al, 2001) and in experimental trials between Asian seabass and brown-marbled grouper . In this study, when exposed to an immersion challenge with a pure culture of betanodavirus, a high percentage of cumulative mortality in the challenge group with manifestations of characteristic clinical signs and conspicuous histopathological lesions has been achieved, which was in accordance with the results reported by Boonyaratpalin et al (1996), Breuil et al (2001, Aranguren et al (2002) and Maeno et al (2007) and Manin and Ransangan (2011) and confirmed the horizontal transmission of betanodavirus through water by immersion exposure. When the Murray cod larvae were imported from the Australian fish farm, viral nervous necrosis virus, Megalocytivirus and Ranavirus detection were carried out by customs using PCR methods.…”
Section: Bath Challenge Experimentssupporting
confidence: 90%
“…These findings indicate that RGNNV type is the most common genotype in tropical and temperate fish species (Curtis et al, 2001;Iwamoto et al, 1999) and has the broadest range of susceptible species (Chi et al, 2003;Ucko et al, 2004). RGNNV type most frequently occurs in the South-East Asian region, where aquaculture practices are developing rapidly (Maeno et al, 2004(Maeno et al, , 2007Yuasa et al, 2007).…”
Section: Bath Challenge Experimentsmentioning
confidence: 87%
“…Regrettably, some authors did not provide the age of the fish in dph, but simply referred to the weight or subjective developmental stage of the fish and categorized them as larvae, juvenile or adults, making it difficult to evaluate the effect of age on infection outcome (Huang et al . ; Maeno, De La Pena & Cruz‐Lacierda ; Lu et al . ; Parameswaran et al .…”
Section: Introductionmentioning
confidence: 99%